1997
DOI: 10.1530/eje.0.1370246
|View full text |Cite
|
Sign up to set email alerts
|

Circulating non-22 kDa growth hormone isoforms in healthy children of normal stature: relation to height, body mass and pubertal development

Abstract: The proportion of non-22 kDa GH isoforms was evaluated in 93 healthy children (48 boys aged 6.8-18.4 years and 45 girls aged 3.9-18.4 years) of normal stature (height Ϯ 2 S.D. score) at different stages of puberty. In addition, correlations among the proportion of non-22 kDa GH isoforms, auxology, spontaneous GH secretion and biochemical measurements were investigated. Serum non-22 kDa GH levels, expressed as percentage of total GH concentration in the samples, were determined by the 22 kDa GH exclusion assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…The fraction of non-22 kDa GH isoforms in our newborns was similar to that in our group of non-pregnant women, despite marked differences in total GH concentrations between the groups. In addition, the neonatal values were also comparable to those reported by us in a group of healthy children at different stages of puberty (29). Hence, the normal proportion of circulating non-22 kDa GH isoforms in our study is in agreement with the previously reported half-life of GH in newborns (19).…”
Section: Total Gh (Mg/l)supporting
confidence: 92%
“…The fraction of non-22 kDa GH isoforms in our newborns was similar to that in our group of non-pregnant women, despite marked differences in total GH concentrations between the groups. In addition, the neonatal values were also comparable to those reported by us in a group of healthy children at different stages of puberty (29). Hence, the normal proportion of circulating non-22 kDa GH isoforms in our study is in agreement with the previously reported half-life of GH in newborns (19).…”
Section: Total Gh (Mg/l)supporting
confidence: 92%
“…Boguszewski et al (15) showed a significant positive correlation between the percentage of non-22K GH isoforms and BMI, weight sd score, or weight for height sd score in prepubertal children. This fact suggested that non-22K GH isoforms may be regulated by nutritional state.…”
Section: Discussionmentioning
confidence: 98%
“…Indirect estimation has been carried out by calculating the difference between total hGH and 22K (15)(16)(17). Other methods employed to estimate 20K include immunoaffinity chromatography (18), electrophoretic systems (19), and gelelectrophoretic-immunostaining-autoradiographic assay (20).…”
Section: Discussionmentioning
confidence: 99%
“…Of the circulating GH moieties in serum, the 22 kDa variant constitutes about two-thirds on the basis of size exclusion chromatography [25], and by far carries the major part of the GH bioactivity as it also has the greatest GH receptor affinity [26]. Some immunoassays, such as the Delfia and the immunofunctional GH assay, measure exclusively or almost exclusively the 22 kDa GH in serum [19, 27, 28]. The other GH variants (di- and polymers and the 20 kDa GH) also have longer plasma disappearance rates than 22 kDa GH, implying that there are several advantages to measuring specifically this variant at the peak level after GH stimulation tests when establishing relevant cut-off levels.…”
Section: Discussionmentioning
confidence: 99%